Assessing emergency department nurses' ability to communicate with angry patients and the factors that influence it - Chen, Xi; Zeng, Yuting; Jiang, Ling; Tian, Lingyun; Yi, Jindong; He, Haiyan; Li, Fang; Long, Yanfang; Li, Li (Frontiers in Public Health, 2023)
Aims To assess emergency department (ED) nurses' ability to communicate with angry patients and to explore the factors that influence nurses' communication skills. Design A cross-sectional survey design. Methods This study was conducted in November and December 2020. Stratified sampling was adopted to recruit ED nurses from 18 tertiary hospitals in western, eastern, and central China to complete an online questionnaire. The Nurses' Communication Ability with Angry Patients Scale (NCAAPS) and the General Self-Efficacy Scale were used to assess ED nurses' communication ability and self-efficacy, respectively. Descriptive statistics, the Mann–Whitney U-test, the Kruskal–Wallis H test, Spearman's correlation analysis, and the generalized linear model were used for data analysis. Results A total of 679 valid questionnaires were collected. The mean total score for the NCAAPS was (3.79 ± 0.47), while the scores for its four dimensions were (3.87 ± 0.59) for communication skills, (3.82 ± 0.59) for anger perception, (3.79 ± 0.53) for self-preparation, (3.73 ± 0.54) for exploring the cause of anger. The generalized linear regression analysis result showed that a longer employment duration, previous communication ability training, and higher self-efficacy were significantly and independently associated with higher NCAAPS scores (p < 0.05). Conclusions The mean total score and the four dimensions score for the NCAAPS were moderate. But there is still room for improvement in ED nurses' ability to communicate with angry patients. “Exploring the cause of anger” was the lowest score among the four dimensions. To improve ED nurses' ability to communicate with angry patients, future studies should focus on constructing specific communication training, improving nurses' ability to explore the cause of anger and self-efficacy. Impact The findings of this study provide important insights into ED nurses' ability to communicate with angry patients and can thus guide the future development of intervention programmes to improve this ability among ED nurses.